Competitive binding of Cd, Ni and Cu on goethite organo–mineral composites made with soil bacteria. (December 2018) - Du, Huihui; Huang, Qiaoyun; Peacock, Caroline L.; Tie, Boqing; Lei, Ming; Liu, Xiaoli; Wei, Xiangdong
Abstract: Soil is a heterogeneous porous media that is comprised of a variety of organo-mineral aggregates. Sorption of heavy metals onto these composite solids is a key process that controls heavy metal mobility and fate in the natural environment. Pollution from a combination of heavy metals is common in soil, therefore, understanding the competitive binding behavior of metal ions to organo-mineral composites is important in order to predict metal mobility and fate. In this study, batch experiments were paired with spectroscopic studies to probe the sorption characteristics of ternary CdNiCu sorbates to a binary organo-goethite composite made with Bacillus cereus cells. Scanning electron microscopy shows that goethite nano-sized crystals are closely associated with the bacterial surfaces. Sorption experiments show a larger adsorptivity and affinity for Cu than Cd/Ni on goethite and B. cereus, and the goethite– B. cereus composite. X-ray photoelectron spectroscopy reveals that carboxylate and phosphate functional moieties present on the bacterial cell walls are primarily responsible for metal sorption to the goethite– B. cereus composite. Synchrotron-based X-ray fluorescence shows that Cu and Ni are predominately associated with the bacterial fraction of the goethite– B. cereus composite, whereas Cd is mainly associated with the goethite fraction. The findings of this research have important implications for predicting the mobility and fate of heavy metals in soil multi-component systems. Graphical abstract: Image 1 Highlights: Larger adsorptivity & affinity for Cu than Cd and Ni on goethite-bacteria composite. Competitive sorption among Cu, Cd and Ni is weaker on composite than on goethite. Cu and Ni are mainly bound to the bacterial fraction of the binary composite. Cd is sorbed mainly on the goethite fraction of the binary composite. Abstract : Cd, Ni and Cu ions compete for similar binding sites on the end-member goethite and B. cereus, but due to different binding affinities, Cu and Ni are mainly bound to the bacterial fraction whereas Cd is predominately sorbed on the goethite fraction of the binary bacteria–mineral composite.